Syria's society upended: Societal rifts pose a massive challenge to pursuit of a political solution - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2017)
The Syrian civil war has profoundly altered established business structures, a delicate balance of religious values, and long-standing ties between urban and rural areas. New networks, identities, and social hierarchies have emerged in connection with the war economy, the militarization of the public sphere, and signs of ethnic cleansing. Any formal end to the conflict is unlikely to halt the violent societal transformation. Co-existence will remain a major challenge due to the nature of the cleavages. However, an inclusive political system that ends the marginalization of the Sunni majority, accepts diversity, and protects minorities is a prerequisite for reducing the levels of profound mistrust between the different societal groups.
Keywords: 320